Analisis Faktor-Faktor yang Mempengaruhi Minat Penggunaan Ulang Paylater pada Generasi Z dan Generasi Milenial - Nafiza Puspa Ayuningtyas Hapsari; Widyastuti, Umi; Aditya, Shandy (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2024)
The aim of this research is to determine the factors that influence interest in reusing paylaters in generation Z and the millennial generation. This study uses a quantitative approach. The purposive sampling technique is a sampling technique and uses the Cochran formula so that 138 respondents are needed using the Partial Least Square (PLS) method. Theoretical studies in this research include TAM theory, Intention to Reuse, Perceived Risk, and Financial technology. The variables in this research include Perceived Effectiveness (X1), Perceived Ease of Use (X2), Perceived Risk (X3), Financial Technology (X4), Attitude Toward Behavior (Z) and Intention to Reuse (Y). The population of this study is generation z and millennial generation who live around the JABODETABEK area. There is a positive and significant influence between perceived usefulness on attitude towards use. There is a positive and significant influence on attitudes towards use. There is a positive and significant influence between risk perception and attitude towards use. There is an insignificant positive influence between financial literacy and attitude towards use. There is a positive and significant influence between perceived usefulness and attitude towards use. There is a positive and significant influence between perceived ease of use and intention to reuse. There is a positive and significant influence on risk perception and intention to reuse paylater, there is a negative and insignificant influence on financial literacy and intention to reuse through attitude to use. There is an insignificant negative influence on perceived usefulness and intention to reuse through attitude to use Keyword: TAM, Shopee paylater, Intention to reuse, Perceived risk, Financial Literacy.